Фабула о продавшемся таланте [A Story of the Man Who Sold His Talent (Publication by Boris Orekhov and Sergei Shaulov)] - Nazirov, Romen (Slavica Revalensia, 2014)
This chapter of the unpublished doctoral dissertation of an expert on Dostoyevsky and literary theory, Romen Nazirov (1934—2004), addresses the problem of how Russian 19th-century literature treated the cultural motif of a deal with the devil. The chapter is centered on an overview of the variants of this motif in the writings of Nikolai Gogol, Vladimir Odoyevsky, Ivan Goncharov, and others.